Targeted deletion of the 9p21 non-coding coronary artery disease risk interval in mice - Visel, Axel; Zhu, Yiwen; May, Dalit; Afzal, Veena; Gong, Elaine; Attanasio, Catia; Blow, Matthew J.; Cohen, Jonathan C.; Rubin, Edward M.; Pennacchio, Len A. (Nature (London), 2010)
Heart disease risk identified It has been know for several years that genetic variations in a stretch of DNA on chromosome 9p21 are linked to the incidence of coronary artery disease. The nature of this link has remained unknown, not least because the 58-kilobase culprit genomic interval contains no known protein-encoding genes, and it appears unlinked to known major contributors to the disease. Now an experiment in which the corresponding stretch of DNA was deleted in mice shows that this part of the chromosome regulates cardiac expression of two genes located some 100,000 base pairs away. The genes, Cdkn2a and Cdkn2b , encode cyclin-dependent kinase inhibitors, and their down-regulation in a mouse model results in excessive aortic smooth muscle cell proliferation. This suggests that dysregulation of vascular cell proliferation underlies cardiac disease susceptibility linked to chromosome 9p21 variation. Sequence variations in a 58-kilobase interval on human chromosome 9p21 have been associated with an increased risk of coronary artery disease. However, this interval contains no protein-coding genes and the mechanism underlying the increased risk has been unclear. Here, the corresponding interval has been deleted from mouse chromosome 4, revealing that this part of the chromosome regulates the cardiac expression of two nearby genes, Cdkn2a and Cdkn2b , and the proliferation dynamics of vascular cells. Sequence polymorphisms in a 58-kilobase (kb) interval on chromosome 9p21 confer a markedly increased risk of coronary artery disease (CAD), the leading cause of death worldwide 1 , 2 . The variants have a substantial effect on the epidemiology of CAD and other life-threatening vascular conditions because nearly one-quarter of Caucasians are homozygous for risk alleles. However, the risk interval is devoid of protein-coding genes and the mechanism linking the region to CAD risk has remained enigmatic. Here we show that deletion of the orthologous 70-kb non-coding interval on mouse chromosome 4 affects cardiac expression of neighbouring genes, as well as proliferation properties of vascular cells. Chr4 Δ70kb/Δ70kb mice are viable, but show increased mortality both during development and as adults. Cardiac expression of two genes near the non-coding interval, Cdkn2a and Cdkn2b , is severely reduced in chr4 Δ70kb/Δ70kb mice, indicating that distant-acting gene regulatory functions are located in the non-coding CAD risk interval. Allele-specific expression of Cdkn2b transcripts in heterozygous mice showed that the deletion affects expression through a cis -acting mechanism. Primary cultures of chr4 Δ70kb/Δ70kb aortic smooth muscle cells exhibited excessive proliferation and diminished senescence, a cellular phenotype consistent with accelerated CAD pathogenesis. Taken together, our results provide direct evidence that the CAD risk interval has a pivotal role in regulation of cardiac Cdkn2a/b expression, and suggest that this region affects CAD progression by altering the dynamics of vascular cell proliferation.